2021
DOI: 10.1111/ane.13548
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cranial nerve palsies following COVID‐19 vaccination—Case report

Abstract: Background The novel COVID‐19 vaccines have side effects that require efficient and close monitoring. Aims of the Study To examine whether the Pfizer‐BioNTech vaccine is associated with multiple cranial neuropathy. Methods We report the case of a 29‐year‐old male patient with no notable history who presented with left oculomotor, abducens, trigeminal and facial palsies 6 days after receiving the first dose of the Pfizer‐BioNTech COVID‐19 vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Manea et al reported on a 29-year-old man who developed multiple cranial neuropathies six days after receiving his first dose of the BNT162b2 vaccine [123]. In particular, he developed incomplete oculomotor (3rd cranial), abducens (6th cranial), and facial (7th cranial) nerve palsies.…”
Section: Ocular Gaze Palsiesmentioning
confidence: 99%
“…Manea et al reported on a 29-year-old man who developed multiple cranial neuropathies six days after receiving his first dose of the BNT162b2 vaccine [123]. In particular, he developed incomplete oculomotor (3rd cranial), abducens (6th cranial), and facial (7th cranial) nerve palsies.…”
Section: Ocular Gaze Palsiesmentioning
confidence: 99%
“…14 Recently, a report of multiple left-sided cranial neuropathies (an incomplete oculomotor palsy without ptosis, partial abducens palsy, hypoesthesia in middle and lower trigeminal nerve distributions, as well as facial nerve palsy-House-Brackmann grade III) has been described in a patient whose symptoms started 6 days after receiving the first dose of the Pfizer-BioNTech SARS-CoV-2 vaccination. 7 No defined mechanism has been identified for cranial nerve palsies following SARS-CoV-2 mRNA vaccination. Post-vaccine nerve palsy could be interpreted as an autoimmune phenomenon, occurring via either mimicry of host molecules by the vaccinal antigen or activation of quiescent autoreactive T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Acute peripheral facial nerve paralysis as an AE following immunisation is a rare adverse reaction (1 of 10 000 to 1 of 1000) described in the product information of SARS-CoV-2 mRNA vaccines. However, the incidence of nerve palsy, including facial, is not reported as being higher than other vaccines, such as the Haemophilus influenzae type B vaccine, the pneumococcal 7-valent conjugate, diphtheria, tetanus, whole-cell pertussis vaccine, as well as measles, mumps and rubella vaccine 3 7 8. Moreover, a recent study demonstrated that the level of reporting of facial nerve palsies after SARS-CoV-2 mRNA vaccination was generally equivalent to those following influenza vaccines prior to the COVID-19 pandemic 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maneaet al1 concluded that "the most probable etiology of the patient's multiple cranial neuropathy is …..COVID-19 vaccine neurological complications." The neurological adverse effect of COVID-19 vaccination is possible.…”
mentioning
confidence: 99%